HIF1 and ID1 Interplay Confers Adaptive Survival to HIF1α-Inhibition - Hao Geng (Frontiers Media S.A., 2021)
Hypoxia is a universal pathological feature of solid tumors. Hypoxic tumor cells acquire metastatic and lethal phenotypes primarily through the activities of hypoxia-inducible factor 1 alpha (HIF1α). Therefore, HIF1α is considered as a promising therapeutic target. However, HIF inhibitors have not proven to be effective in clinical testing. The underlying mechanism is unclear. We report that oncogenic protein ID1 is upregulated in hypoxia by HIF1α shRNA or pharmacological inhibitors. In turn, ID1 supports tumor growth in hypoxia in vitro and in xenografts in vivo, conferring adaptive survival response and resistance. Mechanistically, ID1 proteins interfere HIF1-mediated gene transcription activation, thus ID1 protein degradation is accelerated by HIF1α-dependent mechanisms in hypoxia. Inhibitions of HIF1α rescues ID1, which compensates the loss of HIF1α by the upregulation of GLS2 and glutamine metabolism, thereby switching the metabolic dependency of HIF1α -inhibited cells from glucose to glutamine.